Study of Dry and Wet Cement Mortar Dynamic Properties - Bragov, А.; Lomunov, A.; Kruszka, L. (Проблемы прочности, 2002)
We performed the dynamic tests and studied the dynamic properties under compression of dry and wet cement mortar specimens using the Hopkinson split pressure bar method. As a result, we determined the fracture stresses and their dependence on the applied loading growth rate. It is noteworthy that the strength characteristic of wet material under study is less by 10-15% as compared to the dry one. С использованием метода разрезного стержня Гопкинсона проведены динамические испытания на сжатие образцов цементного раствора в сухом и увлажненном состоянии. Экспериментально определены разрушающие напряжения и их зависимость от роста скорости приложенной нагрузки. Отмечено, что прочность сухого материала на 10...15% превышает прочность материала в увлажненном состоянии. За допомогою методу розрізного стрижня Гопкінсона проведено динамічні випробування на стиск зразків цементного розчину в сухому і зволоженому стані. Експериментально визначено руйнівні напруження й їхню залежність від росту швидкості навантаження, що прикладається. Відмічено, що міцність сухого матеріалу на 10...15% перевищує міцність матеріалу у зволоженому стані.